2021
DOI: 10.1158/0008-5472.can-19-3560
|View full text |Cite
|
Sign up to set email alerts
|

Gain of HIF1 Activity and Loss of miRNA let-7d Promote Breast Cancer Metastasis to the Brain via the PDGF/PDGFR Axis

Abstract: Early detection and adjuvant therapies have significantly improved survival of patients with breast cancer over the past three decades. In contrast, management of metastatic disease remains unresolved. Brain metastasis is a late complication frequently observed among patients with metastatic breast cancer, whose poor prognosis calls for novel and more effective therapies. Here, we report that active hypoxia inducible factor-1 (HIF1) signaling and loss of the miRNA let-7d concur to promote brain metastasis in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Dual-luciferase reporter assays confirmed that Jab1 was a direct regulatory target of let-7d, whereas in vitro assays on MDA-MB-231 and MCF-7 cells and xenograft in vivo assays demonstrated a role for let-7d in regulating breast cancer cell proliferation, invasion and tumor growth in vivo [ 57 ]. Let-7d was also shown to play a role in the development of breast cancer metastasis to the brain [ 62 ]. The loss of let-7d and activation of hypoxia-inducible factor-1 signaling induced brain metastasis via a platelet-derived growth factor (PDGF) pathway in a mouse model of spontaneous breast cancer metastasis from the primary site to the brain: If PDGFR was pharmacologically inhibited, experimental brain metastasis was suppressed, pointing out new therapeutic opportunities [ 62 ].…”
Section: Let-7d and Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Dual-luciferase reporter assays confirmed that Jab1 was a direct regulatory target of let-7d, whereas in vitro assays on MDA-MB-231 and MCF-7 cells and xenograft in vivo assays demonstrated a role for let-7d in regulating breast cancer cell proliferation, invasion and tumor growth in vivo [ 57 ]. Let-7d was also shown to play a role in the development of breast cancer metastasis to the brain [ 62 ]. The loss of let-7d and activation of hypoxia-inducible factor-1 signaling induced brain metastasis via a platelet-derived growth factor (PDGF) pathway in a mouse model of spontaneous breast cancer metastasis from the primary site to the brain: If PDGFR was pharmacologically inhibited, experimental brain metastasis was suppressed, pointing out new therapeutic opportunities [ 62 ].…”
Section: Let-7d and Breast Cancermentioning
confidence: 99%
“…Let-7d was also shown to play a role in the development of breast cancer metastasis to the brain [ 62 ]. The loss of let-7d and activation of hypoxia-inducible factor-1 signaling induced brain metastasis via a platelet-derived growth factor (PDGF) pathway in a mouse model of spontaneous breast cancer metastasis from the primary site to the brain: If PDGFR was pharmacologically inhibited, experimental brain metastasis was suppressed, pointing out new therapeutic opportunities [ 62 ]. An example of another therapeutic approach is the analysis of microRNA as possible indicators of drug sensitivity.…”
Section: Let-7d and Breast Cancermentioning
confidence: 99%
“…Breast cancer ncRNA lncRNA XIST EMT and MSN/c-Met [129] miR-10b - [130] miR-576-3p - [131] lncRNA BCBM lncRNA BCBM /JAK2/STAT3 [132] circBCBM1 circBCBM1/miR-125a/BRD4 axis [133] lncRNA-CCRR lncRNA-CCRR/connexin 43 [134] miRNA let-7d PDGF/PDGFR axis [135] miR-802-5p; miR-194-5p - [136] miR-132-3p; miR-199a-5p; miR-150-5p; miR-155-5p - [137] miR-211 SOX11/NGN2 axis [138] Notes: ESCC: esophageal squamous cell carcinoma; FSCN1: fascin actin-bundling protein 1; VDR: vitamin D receptor; KLF5: Kruppel like factor 5; bHLH transcription factor 2; CDK6: Cyclin Dependent Kinase-6; STAT3: signal transducer and activator of transcription-3; HDAC: histone deacetylase 1; ZEB1: Zinc Finger E-Box Binding Homeobox 1; ROCK1: Rho associated coiled-coil containing protein kinase 1; CRYAB: αB-crystallin; DNMTs: DNA methyltransferase; ERα: estrogen receptor alpha; TET2: ten-eleven translocation 2; IRX1: iroquois homeobox 1; PDK1: phosphoinositide-dependent kinase-1; ST7L: suppression of tumorigenicity 7 like; and BRD4: bromodomain containing 4.…”
Section: Biomarkers Pathways Referencesmentioning
confidence: 99%
“…By modulating connexin 43 expression, dysregulation of lncRNA-CCRR contributes to breast cancer brain metastases through intercellular coupling [134]. Loss of miRNA let-7d and active hypoxia-inducible factor-1 (HIF1) signaling enhances breast cancer brain metastasis via platelet-derived growth factor (PDGF), while pharmacologic inhibition of PDGF receptor (PDGFR) inhibits brain metastasis, implying new therapeutic possibilities [135]. miR-132-3p, miR-199a-5p, miR-150-5p, miR-155-5p, miR-802-5p and miR-194-5p from breast cancer cells also were identified the important role in brain metastasis [136,137].…”
Section: Epigenetics In Brain Metastasismentioning
confidence: 99%
“…• Loss of miRNA let-7d and gain of HIF1 activity promote breast cancer brain metastasis via PDGF; inhibition of PDGFR suppresses brain metastasis [119]. • In pericytes and stromal fibroblasts, the PDGF-BB-PDGFRβ-IL-33-ST2 axis recruits TAMs and induces metastasis [120].…”
Section: Met Ronmentioning
confidence: 99%